Organization of repeated regions within the Epstein-Barr virus DNA molecule. - Hayward, S D (1980)
Virions of human Epstein-Barr virus released from the B95-8 line of marmoset lymphoblasts have linear double-stranded DNA molecules of 115 x 10(6) molecular weight (180 +/- 10 kilobase pairs). Approximately 20% of this DNA yields multiple fragments of 3,200 base pairs when cleaved with any one of the BglII, BamHI, PvuII, SacI, SstII, or XhoI restriction enzymes. The results of cleavage site mapping with these and other enzymes, together with blot hybridization experiments using the 3.2-kilobase pair BglII-R fragment as a probe, indicate that these fragments originate from an internal region between 0.710 and 0.915 map units containing a cluster of at least 12 apparently identical repetitions of a sequence with relatively high guanine plus cytosine content. The repeat units are arranged in adjacent tandem array with all copies having the same orientations, and they form a series of oligomers of tailed double-stranded circles when fragments containing portions of the cluster are denatured and reannealed. Physical maps of cleavage sites within the 3.2-kilobase pair repeat units and in the flanking sequences surrounding the repeat cluster have been constructed. We conclude that the Epstein-Barr virus DNA molecule, like those of other mammalian herpesviruses, may be regarded as being divisible into a large L segment and a smaller S segment. However, the detailed arrangement of repetitive sequences within the Epstein-Barr virus S segment differs significantly from that in all other herpesvirus genomes described so far.